Classroom management that works : research-based strategies for every teacher - Marzano, Robert J.; Marzano, Jana S.; Pickering, Debra (Alexandria, VA : Association for Supervision and Curriculum Development, 2003)
Discusses the importance of classroom management to effective teaching and learning, and draws from educational research to present specific strategies teachers can use to control their classrooms, covering rules and procedures, disciplinary interventions, teacher-student relationships, student responsibility, and other topics.
Includes bibliographical references (p. 126-137) and index.
Professional
Keywords: Classroom management -- United States; Effective teaching -- United States; Classroom management; Teaching -- United States